IFN-γ, IL-2, IP-10, and MIG as Biomarkers of Exposure to Leishmania spp., and of Cure in Human Visceral Leishmaniasis - Ibarra-Meneses, Ana V.; Ghosh, Prakash; Hossain, Faria; Chowdhury, Rajashree; Mondal, Dinesh; Alvar, Jorge; Moreno, Javier; Carrillo, Eugenia (Frontiers in Cellular and Infection Microbiology, 2017)
New biomarkers are needed for monitoring the effectiveness of treatment for visceral leishmaniasis (VL). They might also improve the detection of the asymptomatic population in Leishmania-endemic areas. This paper examines the IL-2, IFN-g, IFN-g-induced protein 10 (IP-10) and monokine-induced-by-IFN-g (MIG) levels in whole blood - stimulated in vitro with soluble Leishmania antigen (SLA) - taken from asymptomatic individuals and patients treated for VL living in a post-outbreak (L. infantum) area in Spain, and in an endemic (L. donovani) area of Bangladesh. IP-10 was found to be an accurate global marker of asymptomatic subjects with positive cellular/humoral tests, while MIG was found to be a better marker of contact with L. donovani than IL-2 but no for those with L.infantum. Determining IP-10, MIG and IFN-g levels proved useful in monitoring the cellular immune response following treatment for active disease caused by L. infantum.